Evolution of Cationic Vacancy Defects: A Motif for Surface Restructuration of OER Precatalyst - Wu, Yi‐jin; Yang, Jian; Tu, Teng‐xiu; Li, Wei‐qiong; Zhang, Peng‐fang; Zhou, Yao; Li, Jian‐feng; Li, Jun‐tao; Sun, Shi‐Gang (Angewandte Chemie International Edition, 2021)
Defects have been found to enhance the electrocatalytic performance of NiFe‐LDH for oxygen evolution reaction (OER). Nevertheless, their specific configuration and the role played in regulating the surface reconstruction of electrocatalysts remain ambiguous. Herein, cationic vacancy defects are generated via aprotic‐solvent‐solvation‐induced leaking of metal cations from NiFe‐LDH nanosheets. DFT calculation and in situ Raman spectroscopic observation both reveal that the as‐generated cationic vacancy defects tend to exist as VM (M=Ni/Fe); under increasing applied voltage, they tend to assume the configuration VMOH, and eventually transform into VMOH‐H which is the most active yet most difficult to form thermodynamically. Meanwhile, with increasing voltage the surface crystalline Ni(OH)x in the NiFe‐LDH is gradually converted into disordered status; under sufficiently high voltage when oxygen bubbles start to evolve, local NiOOH species become appearing, which is the residual product from the formation of vacancy VMOH‐H. Thus, we demonstrate that the cationic defects evolve along with increasing applied voltage (VM → VMOH → VMOH‐H), and reveal the essential motif for the surface restructuration process of NiFe‐LDH (crystalline Ni(OH)x → disordered Ni(OH)x → NiOOH). Our work provides insight into defect‐induced surface restructuration behaviors of NiFe‐LDH as a typical precatalyst for efficient OER electrocatalysis. Along with increasing voltage during the OER process, the structural evolution of cationic defects within NiFe‐LDH, where the simple vacancy VM changes to VMOH and then to the most reactive VMOH‐H, and the surface restructuration, where surface crystalline Ni(OH)x is converted to disordered Ni(OH)x and then to the surface local NiOOH species, are voltage‐regulated concurrent events defining the eventual catalytic performance of the precatalyst.